(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
This article analyzes the interrelationship between creativity and reflection in music education from a psychological and pedagogical perspective. The study emphasizes that creativity and reflection are not separate processes but mutually reinforcing mechanisms that shape the professional and artistic development of future music teachers. Reflection provides self-awareness, emotional regulation, and analytical understanding, while creativity transforms reflective insight into new musical ideas and pedagogical innovations. Drawing on the works of both international and Uzbek scholars, the article highlights how reflective practice enhances creative expression, metacognition, and emotional intelligence in music learning. The findings contribute to modernizing music pedagogy and strengthening reflective-creative competencies in teacher training programs.